The relationship of kidney function, cardiovascular morbidity and all-cause mortality: A prospective primary care cohort study - Kiiski, Sem (My University, 2023)
BACKGROUND: Lower than normal estimated glomerular filtration rate (eGFR) is associated with the risk for all cause mortality and adverse cardiovascular events. In this regard, the role of higher than normal eGFR is still controversial. OBJECTIVE: Investigate long term clinical consequences across the levels of eGFR calculated by the creatininebased Chronic Kidney Disease Epidemiology Collaboration (CKD EPI) equation among apparently healthy cardiovascular risk subjects. DESIGN: Prospective study. PARTICIPANTS: Participants (n=1747) of a populationbased screening and intervention program for cardiovascular risk factors in Finland during the years 2005 2007. MAIN MEASURES: Cardiovascular morbidity and allcause mortality. KEYRESULTS: Overthe14 yearfollow up,subjects with eGFR 105 ml/min/1.73 m 2 (n=97) had an increased risk for all cause mortality [HR 2.15 (95% CI: 1.24 3.73)], incident peripheral artery disease [HR 2.62 (95% CI: 1.00 6.94)], and atrial fibrillation/flutter [HR 2.10 (95% CI: 1.21 3.65)] when compared to eGFR category 90 104 ml/min after adjustment for cardiovascular and lifestyle related risk factors.The eGFRcategory 105 ml/ min was also associated with a two fold increased mortality rate compared to the Finn ish general population. CONCLUSIONS: Renal hyperfiltration defined as eGFR 105 ml/min/1.73 m 2 is a frequent and important finding in patients commonly treated in primary care. These patients should be followed closely for timely interventions, such as strict BP and blood glucose regulation.
Keywords: glomerular filtration rate, renal hyperfiltratio, mortality, cardiovascular diseases